MODERN DIRECTIONS AND APPROACHES TO DEVELOPING CREATIVE COMPETENCIES IN HIGHER EDUCATION STUDENTS (SCIENCE TIME JOURNAL, 2026)
In this article, the author talks about modern approaches to developing creative competencies in higher education students. Moreover, the author explains about the importance of the approaches. The author demonstrates information based on foreign sources.